2017
DOI: 10.1159/000484932
|View full text |Cite
|
Sign up to set email alerts
|

ZNF750 Expression Is a Potential Prognostic Biomarker in Esophageal Squamous Cell Carcinoma

Abstract: Objective: ZNF750, a transcriptional regulator of epidermal differentiation, has been identified as a tumor suppressor in esophageal squamous cell carcinoma (ESCC). The aim of the present study was to investigate the clinical and prognostic significance of ZNF750 expression and to evaluate the effect of ZNF750 knockdown on cell proliferation, migration, and invasion in ESCC. Methods: A total of 124 patients with ESCC who underwent curative esophagectomy were evaluated in this study. The expression of ZNF750 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 27 publications
0
16
1
Order By: Relevance
“…The present study also detected FGFR2 mutations in iCCA, and demonstrated that they mainly occurred in patients older than 70 years, which implies that the mutation of FGFR2 was associated with the age of Chinese patients with CCA. ZNF750 has been reported as a prognostic biomarker in ESCC (55). Although only two mutations of ZNF750 were detected in the present study, notably, both mutations occurred in group IV (>70 years).…”
Section: Discussioncontrasting
confidence: 68%
“…The present study also detected FGFR2 mutations in iCCA, and demonstrated that they mainly occurred in patients older than 70 years, which implies that the mutation of FGFR2 was associated with the age of Chinese patients with CCA. ZNF750 has been reported as a prognostic biomarker in ESCC (55). Although only two mutations of ZNF750 were detected in the present study, notably, both mutations occurred in group IV (>70 years).…”
Section: Discussioncontrasting
confidence: 68%
“…633 (95% CI, 0.557 to 0.709). Figure 3D and 3E showed the prognosis ability of our CHRNB4 and prognostic nomogram (AUC=0.84) are as good as or even better than TNM, CD59, and ZNF750 (AUC=0.64, 0.64, respectively), which were previously published biomarkers in ESCC (22,23). The survival curve for the probability of survival of the nomogram is shown in Figure 3F (P =0.03).…”
Section: Chrnb4-based Forecast Model and Prognostic Nomogram To Predimentioning
confidence: 57%
“…However downstream targets of ZNF750 have been recently discovered, elucidating possible alternative targeting strategies for this pathway. Reduced ZNF750 expression also predicts more aggressive esophageal SCC, making it possible that detecting its loss in SeC may help identify the small proportion of tumors that recur and metastasize. Additional study correlating ZNF750 expression with clinical follow‐up data is necessary to assess if ZNF750 truly correlates with clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%